2005
DOI: 10.1111/j.1475-6773.2005.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Geography and Spatial Behavior on Health Care Utilization among the Residents of a Rural Region

Abstract: Objective. This analysis determines the importance of geography and spatial behavior as predisposing and enabling factors in rural health care utilization, controlling for demographic, social, cultural, and health status factors. Data Sources. A survey of 1,059 adults in 12 rural Appalachian North Carolina counties. Study Design. This cross-sectional study used a three-stage sampling design stratified by county and ethnicity. Preliminary analysis of health services utilization compared weighted proportions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
340
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(365 citation statements)
references
References 21 publications
16
340
1
8
Order By: Relevance
“…[61][62][63][64][65][66][67][68][69][70][71] Several studies have found that women who lived farther away from facilities were less likely to undergo mammography than those who lived closer to facilities. [72][73][74][75][76] Contrary to those results, a study of the relationship between distance or travel time and adherence to screening mammography recommendations in rural Michigan failed to find an association.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65][66][67][68][69][70][71] Several studies have found that women who lived farther away from facilities were less likely to undergo mammography than those who lived closer to facilities. [72][73][74][75][76] Contrary to those results, a study of the relationship between distance or travel time and adherence to screening mammography recommendations in rural Michigan failed to find an association.…”
Section: Discussionmentioning
confidence: 99%
“…El papel de los determinantes primarios ambientales, entre los que se pueden incluir las características del proveedor, del sistema de atención o el entorno físico están ampliamente estudiadas 4,5 . Las características de los individuos pueden agruparse en unos factores predisponentes como la ocupación, la estructura social o la educación; otros facilitadores como el nivel de renta , la existencia de aseguramiento o la accesibilidad de los servicios o los tiempos de espera; y la «necesidad», como principal elemento generador de demanda sanitaria, que a su vez tiene un componente objetivable y otro de percepción.…”
Section: Introductionunclassified
“…Geographic accessibility and proximity to health care clinics have a direct influence on the development of health care services (Arcury et al, 2005;Buor, 2003;Gething et al, 2004;Tanser et al, 2006). In South Africa, the temporal and spatial coverage by public transport is sporadic, unreliable and expensive.…”
Section: Introductionmentioning
confidence: 99%